Sistem Pakar untuk Mendiagnosa Gangguan pada Sistem Endokrin Berbasis Android Mobile - Irawan Setiadi; Imam Himawan; Kevin Septianzah (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2023)
This research discusses how to design an expert system that can be used to diagnose disorders of the endocrine system based on the symptoms suffered by the patient, so that there are advice on the problems encountered by the user. The objective is to assist prospective doctors, general practitioners and specialists in diagnosing disorders of the endocrine system like an expert, to provide information quickly, and to create an interactive application that can be easily understood by the users. The expert system is created using the Best-First Search method and using the Forward Chaining technique. The system contains the knowledge of an expert obtained during research at Permata Ibu Hospital and a knowledge base designed to be able to store new diseases. The expert system is developed based on smartphone technology or more specifically Android on the client side, PHP (Hypertext Preprocessor) and MySQL base on the server side. The system contains 6 disease data and 10 disease symptom data. It also has been tested and validated by experts and several users. The result reaching a percentage of 83.3% shows that the expert system application is quite efficient and effective.